Strategies to Improve Children's Motor Skills with Special Needs Through Circuit Method Based Inclusion Education - Gatot Jariono; Nurhidayat; Prita Yunita; Satria Yudi Gontara; Haris Nugroho; Uzizatun Maslikah (UNIB Press, 2023)
Circuit based inclusion education is the learning of motion activities through the circuit method which is divided into several posts to improve motor skills according to the characteristics of children with needs special. The population and samples in this study were students at the Sukoharjo state extraordinary school totaling 30 people, sampling technique using purposive sampling. The data collection technique using tests and measurements of motor ability k consists of a 20-meter running test, hand eye coordination, agility, and explosive power of the leg muscles. The t-test used in data analysis with a significance level of α = 0.05. The results of this study show that the teacher's strategy in improving the motor skills of children with special needs consists of teachers as companions, mediators, motivators and artists. Thus, it can be concluded that circuit-based inclusion education can improve the motor skills of children with special needs. However, it is necessary to conduct further research by considering social environmental factors, psychosocial, physical components, and those related to improving the motor abilities of children with special needs.